C-Reactive Protein Causes Adult-Onset Obesity Through Chronic Inflammatory Mechanism - Li, Qiling; Wang, Qi; Xu, Wei; Ma, Yamin; Wang, Qing; Eatman, Danita; You, Shaojin; Zou, Jin; Champion, James; Zhao, Lanbo; Cui, Ye; Li, Wenzhi; et al. (Frontiers in Cell and Developmental Biology, 2020)
Obesity is characterized by low-grade chronic inflammation. As an acute-phase reactant to inflammation and infection, C-reactive protein (CRP) has been found to be the strongest factor associated with obesity. Here we show that chronic elevation of human CRP at baseline level causes the obesity. The obesity phenotype is confirmed by whole-body magnetic resonance imaging (MRI), in which the total fat mass is 6-9 folds higher in the CRP rats than the control rats. Univariate linear regression analysis showed different growth rates between the CRP rats and the control rats, and that the difference appears around 11 weeks old, indicating that they developed adult-onset obesity. We also found that chronic elevation of CRP can prime molecular changes broadly in the innate immune system, energy expenditure systems, thyroid hormones, apolipoproteins, and gut flora. Our data established a causal role of CRP elevation in the development of adult-onset obesity.